Penicillium thailandense (Aspergillaceae, Eurotiales), a new species isolated from soil in northern Thailand - Khuna, Surapong; Kumla, Jaturong; Thitla, Tanapol; Hongsanan, Sinang; Lumyong, Saisamorn; Suwannarach, Nakarin (Phytotaxa, 2023)
A new species of soil fungi, described herein as Penicillium thailandense, was isolated from soil samples of deciduous dipterocarp forest in Lamphun Province, Thailand. This species was identified by using combination of morphological characteristics and molecular analyses. Morphologically, P. thailandense is similar to P. sanjayi, but it can be distinguished by having monoverticillate and biverticillate conidiophores, white to dark gray sclerotia, and larger conidia. Multi-gene phylogenetic analyses of a combination of the internal transcribed spacer (ITS) of ribosomal DNA, β-tubulin (BenA), calmodulin (CaM), and RNA polymerase II second largest subunit (rpb2) genes revealed that P. thailandense belongs to the Penicillium section Citrina and is distinct from other known species. This paper provides a description, illustrations, and phylogenetic tree of this novel species.